Exercise as a protagonist in muscle plasticity and in the muscle as an endocrine organ: implications in chronic diseases: El ejercicio como protagonista en la plasticidad muscular y en el músculo como un órgano endocrino: implicaciones en las enfermedades crónicas - Vargas-Pacheco, Amelia (2021)
The active skeletal muscle and the maintenance of muscle mass are essential for good health, wellness and disease prevention and treatment. The muscle as an endocrine organ capable of synthesizing   myokines, has been documented recently. These peptides are secreted as a response to muscular contractions induced by exercise, and can develop molecular communication with other tissues, improving cardiovascular, metabolic, and mental health. The endocrine function of a muscle continues to be in a constant investigation; however, knowledge up to date urge us to continue promoting physical activity. Additionally, the extended knowledge of myokins is useful to prescribe individualized physical exercise programs to each patient.